Fuzzy n-s-homogeneity and fuzzy weak n-s-homogeneity - Samer Al Ghour; Almothana Azaizeh (Institute of Advanced Engineering and Science, 2019)
Fuzzy n-s-homogeneity and fuzzy weak n-s-homogeneity are introduced in fuzzy bitopological spaces. Several relationships, characterizations and examples related to them are given.